Factores psicosociales que inciden en la satisfacción de necesidades de habitabilidad de las 32 familias reasentadas, en la primera etapa de urbanización ciudad Victoria, de la ciudad de Guayaquil - Jaramillo Muñoz, Pablo Marcelo (2014)
This research raises the premise, that the satisfaction of needs of habitability , including three dynamic areas relating to personal, relational and collective needs , realize a balance in the quality of life in human settlements , in turn directly related with space. In this sense, this research has taken the experience of a Housing Project called Victoria as scenario analysis of the relationship of these variables. The housing project goes through several events that show the process of change and adaptation of a group of 32 families initially was in informal settlements, to become resettled in that housing project. As a theoretical basis analysis realizes an integration of theories of environmental and community psychology offers insights into the understanding of the living conditions of these families. Therefore, the human being in his ability to inhabit in all its facets, is the center, the why and wherefore of institutional interventions and research . In this sense, the concept of habitability is rector of the whole process of the social production of habitat and construction of urban- architectural works .